A Critical Flow Model for Supercritical Pressures - Lv, Yufeng; Zhao, Minfu; Du, Kaiwen (Frontiers in Energy Research, 2020)
The investigation of critical flow model for supercritical pressure condition is relatively rare. Based on isentropic flow and thermal equilibrium assumptions, a model is derived to calculate discharge flow rate and critical pressure. Considering the influence of friction and local resistance, a correction coefficient is added which can be calculated from CFX analysis software. The model avoids the calculation of quality and is applicable to wide range which covering the subcooled water, two-phase mixture, steam critical flow under subcritical pressure and supercritical pressure. Reasonable agreement is shown between model predicted results and experiment data, illustrating the accuracy of the proposed model.